PENERAPAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS XI SMA MUHAMMADIYAH 1 PEKANBARU - Maharani Maharani; Zuhdi Ma’aruf; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to describe the cognitive learning outcomes of students in learning physics on the material elasticity and Hooke's law through the application of the Team Assisted Individualization (TAI) learning model in class XI of Muhammadiyah 1 Pekanbaru Senior High School and to know the differences in students' cognitive learning outcomes in learning physics on elasticity and Hooke's law through the application of the Team Assisted Individualization class XI learning model at SMA Muhammadiyah 1 Pekanbaru. This type of research is a quasi-experimental design with a posttest-only design. The research subjects were class XI MIA 2 as an experimental class and class XI MIA 3 as a control class. Data collection instruments using cognitive learning test results. Data were analyzed using descriptive and inferential analysis. The results showed there were differences in student learning outcomes that apply the TAI learning model with conventional learning. Classroom learning outcomes with the TAI learning model is 83.03%, while the class with conventional learning is 7607%. Thus it can be concluded that the application of the TAI model can improve the learning outcomes of students of class XI MIA SMA Muhammadiyah 1 Pekanbaru on the material elasticity and Hooke's law.Key Words: Cognitive Learning Outcomes, Elasticity and Hooke's Law, Team Assisted Individualization